A resiliência do direito do trabalho - Alencar, Eduardo Fornazari (2020)
Resiliência do Direito do Trabalho is a topical and well-timed subject because configurates itself as a way of understanding how the Law dinamic works and, more precisely, the Labor Law dinamic, in a contemporary society, facing up changes repeatdly, while preserving its general balance, structure and identity. This present thesis aims ascertain whether Labor Law is resilient, how and why this resilience could be effected, also its consequences. For this purpose, an approach on constitutent elements of the subject was made based on extensive books, articles and periodicals research. Initially, it is undertaken the legal system framing as an autopoietc system, building it on the Niklas Luhmann’s systems theory. Thereafter, the resilience is studied, its concept, meanings and patterns. Subsequently, this work analyses the Labour Law pluralismo as the justifier aspect of its resilience. After the subject elements had been analysed, it must be concluded that the Labor Law is resiliente and its resilience is due primarily to its pluralism. Lastly, the consequences of that are identified